Recycling of Polystyrene Waste in the Composition of Ecological Mortars. (2015) - Aciu, Claudiu; Manea, Daniela Lucia; Molnar, Luminita Monica; Jumate, Elena
Abstract: As part of sustainable development, an important objective of constructors is the elaboration of a technology that may lead to the manufacture of new building materials and their implementation so as to contribute to the protection of the environment and natural resources, as well as to the creation of healthy living conditions. This study presents technologies for the manufacture of new building materials by polystyrene waste recycling. The following are produced: an ecological plastering mortar whose thermal conductivity is three times lower than that of ordinary mortar, which recommends it as a thermal insulation plastering mortar; three thermal insulation fillers, of which one is also recommended to be used as panels for external thermal insulation systems. All these are supported by the results obtained following the laboratory determinations presented in the paper.